China‘s responsibility for the COVID – 19 pandemic: an international law perspective - Piepolis, Andrius; Smilgevičiūtė, Kamilė (Vilnius University Open Series, 2021)
This article focuses on state responsibility elements under international law and analyses legal preconditions for China‘s responsibility under international law for COVID-19 pandemic management related actions.